Ticks species (Acari: Ixodidae) parasites of dogs (Canis familiaris) in urban areas from Mendoza province, Argentina (FAVE Sección Ciencias Veterinarias, 2018)
Knowledge of the ectoparasitic agents of pets has implications both in veterinary medicine and public health since several agents have the potential to spread from animal to human and vice versa. Ticks sent to the Centro de Investigación en Parasitología Regional (CIPaR) during 2010 to 2013 were analysed. 466 adult ticks were collected from 217 dog in urban areas from Mendoza province, Argentina. Of these, 83.5% (n=385) specimens were identified as Rhipicephalus sanguineus s.l. (84 male and 199 female – ratio 1:2.37 –, 65 nymphs and 37 larvae), while 16.5% (n = 76) were identified as Amblyomma tigrinum (10 males and 61 females – ratio 1:6.1 –, and five adults in bad condition, which precluded their sexing). In addition, five adult specimens, identified as Amblyomma, were not identified to the species level since they were fully engorged. This report is an important contribution to the knowledge of the species of ticks in dogs (Canis familiaris) in the province of Mendoza.
Keywords: ticks; Rhipicephalus sanguineus; Amblyomma tigrinum; Mendoza; dogs